The Effect of Bank Characteristics on Return on Asset with Macroeconomics as Moderation - Dadang Agus Suryanto; Sussy Susanti; Sugiyanto Ikhsan (International Journal of Economics Development Research (IJEDR), 2023)
The banking industry as a sub-system of the financial services industry is often considered as one of the determinants in the course of a country's economy, because banking can be used as a barometer of a country's economic stability. Healthy bank growth is a sign of an improving country's economy, so from a macro perspective it is an important industry that gets attention from the government. Profitability is one of the references for banking performance, the higher the profit earned indicates the company's performance is good. Return on Asset (ROA) as an indicator of financial success used to determine the efficiency of a business in creating profits through the utilization of its total assets. An increase in ROA indicates that the bank company has strong future prospects due to opportunities for profit growth. Therefore, to maintain or increase ROA, it is necessary to pay attention to influencing factors, including Capital Adequacy Ratio (CAR), Loan To Deposit Ratio or Loan To Funding Ratio (LDR / LFR) and Non Performing Loan (NPL) as well as economic growth (GDP) and Inflation as macroeconomics that have an impact on the people's economy. This research uses a quantitative approach, using data from state-owned banks during 2010-2020. Data analysis using multiple regression tests previously carried out classical assumption tests, so as to obtain research results that are relevant to the state of banking companies. The results showed that partially NPL, GDP, and Inflation have an influence on ROA, while CAR and LDR have no influence on ROA. The moderation model shows that GDP is able to moderate CAR, NPL. and Inflation, while Inflation is only able to moderate NPL and GDP.